Performance evaluation of maize genotypes in far western hills of Nepal - Hari Kumar Prasai (Azarian Journal of Agriculture, 2015)
Twenty one maize genotypes in Intermediate Yield Trial (IYT) and fourteen genotypes in Coordinated Varietal Trial (CVT) were evaluated at Bhagetada, Dipayal, Doti, Nepal in 2012 and 2013 during summer seasons. The trials were laid out in randomized complete block design with three replications. The combined analysis of IYT trials over years showed that Rampur SO3FO8, Across 9531 (RE), RPOP-1 and BLSBSO7-F12 were high yielding genotypes whereas the combined analysis of CVT trials over two years showed that RPOP-3 RPOP-2 and RPOP-4 were high yielding genotypes. The combined analysis of common genotypes (from IYT and CVT) over two years showed that higher grain yielding genotypes were RPOP-1 (3561 kg/ha), RPOP-2 (3464 kg/ha), RPOP-3 (3371 kg/ha) and RPOP-4 (3259 kg/ha).They were promising genotypes however should be tested at on-farms before promoted for general cultivation in river basin agro environment of far western hills of Nepal.